Back To Birmingham : Richard Arrington, Jr., and His Times - Franklin, Jimmie Lewis (Book collections on Project MUSE., 1989)
In the 1960's, Birmingham, Alabama was a battleground in the struggle for human rights in the American South. In 1979 the city that had once used dogs and fire hoses to crush protest demonstrations elected a black mayor, Richard Arrington, Jr. The author, Franklin, relies heavily on primary sources, personal interviews, and newspapers to tell his story. Richard Arrington, Jr. was destined to bring about some fundamental changes in the city, once known for it's defiance of racial equality and progress.